(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of using a nutritional product containing synbiotics on the anthropometric status of children aged 24-59 months in Phu Luong district, Thai Nguyen province. Subject and methods: A community intervention study with a control group was conducted, involving 640 children who were randomly assigned to two groups based on anthropometric indices, age, and gender. The intervention group consumed the nutritional product containing synbiotics for 4 months, with a dosage of 2 sachets per day from Monday to Friday each week. Anthropometric indices were classified according to WHO 2006 standards. Results: The mean weight and height after 2 and 4 months in the intervention group increased significantly more than in the control group (p<0.001). The mean WAZ after 2 months increased by 0.11 ± 0.19 and 0.04 ± 0.14, respectively, and after 4 months by 0.12 ± 0.20 and 0.06 ± 0.19 (p<0.001). The mean WHZ after 2 months increased by 0.16 ± 0.32 and 0.04 ± 0.24, respectively, and after 4 months by 0.16 ± 0.31 and 0.09 ± 0.31 (p<0.05) compared to baseline (T0). Conclusions: The intervention using a nutritional product containing synbiotics showed significant effects on anthropometric indices after 2 and 4 months. Therefore, the proposed product and intervention method are suitable to prevent and treat children at risk of wasting.